Analisis Kinerja Keuangan Perusahaan Terdaftar Di BEI Sebelum dan Selama di Berlakukan Masyarakat Ekonomi ASEAN (MEA) ( Studi Kasus Pada Perusahan Sektor Industri Barang Konsumsi - Laiya, Novita (Universitas Sam Ratulangi, 2019)
The results of the study at Î± = 0.05 in general in the consumer goods industry sector companies showed that out of the 5 hypotheses proposed there were no significant hypotheses affected by the implementation of the ASEAN Economic Community (AEC). Whereas if viewed from the results of the analysis based on each sub-sector, the food and beverage sub-sector is the sub-sector most affected by the implementation of the ASEAN Economic Community (AEC), where there are three significant indicators namely DAR = 0.001, DER = 0.010 and AT0 = 0.036, while in other sub-sectors there is no significant hypothesis. Measures that can be taken to overcome the impact of the ASEAN Economic Community (AEC) reduce the use of imported raw materials by utilizing natural resources in the country.Keywords : Financial Performance assessment, The Asean Economi Community (AEC) Financial RatioÂ